Propuesta de un sistema de planificación de la demanda para optimizar la gestión de compras e inventarios en una empresa del sector marítimo de Cartagena de Indias - López, Andrés Camilo Julio (My University, 2026)
The objective of this research is to propose a demand planning system aimed at optimizing procurement and inventory management in a maritime sector company located in Cartagena de Indias. The study was conducted using a quantitative, descriptive, and propositional approach, based on the analysis of historical data extracted from the company's ERP system for the year 2025. The diagnostic results showed that the company maintains an active inventory of 932 items, with an economic value of USD 1,684,158, despite operating under a predominantly stock / non-stock policy. A high concentration of inventory value was identified, with spare parts and materials for major maintenance accounting for more than 84% of the total value, and 52% of the items having an age exceeding three years. In the procurement process, 60.5% of requisitions are managed under priority handling schemes, reflecting a strong reactive orientation. Additionally, the average approval time for purchase orders was found to be 4.4 days. Based on these findings, different demand planning models were evaluated, and a structured system was formulated that integrates item classification, the definition of differentiated planning approaches, and the calculation of operational parameters, articulated with procurement and inventory processes. Finally, the cost-benefit analysis demonstrated the economic feasibility of the proposed system, highlighting its potential to reduce urgent purchases, improve operational efficiency, and strengthen data-driven decision-making. [resumo fornecido pelo autor]
La presente investigación tiene como objetivo proponer un sistema de planificación de la demanda orientado a optimizar la gestión de compras e inventarios en una empresa del sector marítimo ubicada en Cartagena de Indias. El estudio se desarrolló bajo un enfoque cuantitativo, de tipo descriptivo y propositivo, a partir del análisis de información histórica extraída del sistema ERP correspondiente al año 2025. El diagnóstico evidenció que la empresa mantiene un inventario activo de 932 ítems, con un valor económico de USD 1.684.158, pese a operar bajo una política predominantemente stock / no stock. Se identificó una alta concentración del valor del inventario, donde los repuestos y materiales para mantenimientos mayores representan más del 84% del valor total, así como una antigüedad superior a tres años en el 52% de los ítems. En el proceso de compras, el 60,5% de los requerimientos se gestiona bajo esquemas de atención prioritaria, reflejando una marcada orientación reactiva. Asimismo, se detectó que el tiempo promedio de aprobación de las órdenes de compra es de 4,4 días. Con base en estos resultados, se evaluaron distintos modelos de planificación de la demanda y se formuló un sistema estructurado que integra la clasificación de ítems, la definición de enfoques diferenciados de planificación y el cálculo de parámetros operativos, articulados con los procesos de compras e inventarios. Finalmente, el análisis costo?beneficio evidenció la viabilidad económica del sistema propuesto, destacando su potencial para reducir compras urgentes, mejorar la eficiencia operativa y fortalecer la toma de decisiones basada en datos. [resumo fornecido pelo autor]
Keywords: Administração de material; Cadeia de suprimentos; Compras - Administração; Controle de estoque; Sistemas de informação gerencial; Eficiência organizacional; Logística empresarial; Materials management; Supply Chain; Shopping - Management; Inventory control; Management information systems; Organizational effectiveness; Business logistics